Preoperative Gastric Residual Volumes in Fasted Patients Measured by Bedside Ultrasound: A Prospective Observational Study. Issue 6 (November 2018) - Ohashi, Y.; Walker, J. C.; Zhang, F.; Prindiville, F. E.; Hanrahan, J. P.; Mendelson, R.; Corcoran, T.
The purpose of this prospective observational study was to measure gastric volumes in fasted patients using bedside gastric ultrasound. Patients presenting for non-emergency surgery underwent a gastric antrum assessment, using the two-diameter and free-trace methods to determine antral cross-sectional area. Gastric residual volume (GRV) was calculated using a validated formula. Univariate and multivariable analyses were performed to examine any potential relationships between 'at risk' GRVs (>100 ml) and patient factors. Two hundred and twenty-two successful scans were performed; of these 110 patients (49.5%) had an empty stomach, nine patients (4.1%) had a GRV >100 ml, and a further six patients (2.7%) had a GRV >1.5 ml/kg. There was no significant relationship between 'at risk' GRV and obesity, diabetes mellitus, gastro-oesophageal reflux disease or opioid use, although our study had insufficient power to exclude an influence of one or more of these factors. Our results indicate that despite compliance with fasting guidelines, a small percentage of patients still have GRVs that pose a pulmonary aspiration risk. Anaesthetists should consider this background incidence when choosing anaesthesia techniques for their patients. While future observational studies are required to determine the role of preoperative bedside gastric ultrasound, it is possible that this technique may assist anaesthetists in identifying patients with 'at risk' GRVs.